STUDIES ON BIO-EFFICACY OF FORMULATIONS OF CARBENDAZIM WITH MANCOZEB 75 WP FOR THE MANAGEMENT OF LATE LEAF SPOT AND RUST OF GROUNDNUT - GURURAJ SUNKAD, (The Bioscan, 2012)
Three formulations of Carbendazim+Mancozeb75 WP, a combi fungicide molecule, two systemic (Hexaconazole and Carbendazim) and two non-systemic (Mancozeb and Chlorothalonil) fungicides were evaluated in vivo for the management of late leaf spot of groundnut and their effect on dry pod and fodder yield. Foliar application of Carbendazim with Mancozeb @ 2g/L was found to be highly effective in the management of late leaf spot and rust of groundnut with higher pod yield (2768 kg/ha) and benefit cost ratio (2.50). Further, Carbendazim+Mancozeb @ 2 g/L was superior not only in controlling diseases, but also resulted in higher percent increase in pod yield in farm trials and large scale demonstration trials conducted in farmers fields. Based upon the results in experimental as well as farm and large scale demonstration trials, Carbendazim+ Mancozeb75 WP @ 2g/L has been recommended as an alternate fungicide molecule to Hexaconazole and included in the university package of practices (POP) of University of Agricultural Sciences, Raichur, Karnataka for the management of rust and late leaf spot of groundnut.